An approach to involve municipal leaders into strategic decision-making for sustainability—A case study - Wälitalo, Lisa; Robèrt, Karl-Henrik; Broman, Göran (Frontiers in Sustainable Cities, 2022)
In a previous study we tested a model for implementation of methodological support for cross-sectoral collaboration for strategic transition toward sustainability. To make the model viable long-term, practitioners emphasized the importance to recruit and engage leaders into the process upfront, however, this was also the key missing element according to the ten municipalities and regions in the action research project. Nevertheless, if addressed sufficiently, active leadership could favor other needed support, such as capacity building and merging with ongoing work. Therefore, this study aimed to design, test and evaluate an approach to better involve leaders into strategic decision-making for sustainability early on in the collaboration processes. The approach evolved as an in-depth study in one of the municipalities. A pre-assessment based on semi-structured interviews and desktop review was compiled and presented back to municipal top management during a session that included a focus group discussion to capture the leaders' feedback on the assessment as well as advice on how to make the implementation model viable long-term. Results gave that the leaders reached a good understanding of the implementation model and how current practice in the municipality related or could be related to it. As an indicator of spurred engagement and hence, a successful result, one outcome from the session was a strategic decision to carry out a thorough sustainability analysis according to the methodology that the model is supposed to implement. This work is ongoing. In addition, support for alignment with existing management systems was asked for. An evaluation of the approach itself was positive, however, pointed at the extensive work needed for the assessment. Alternative ways, such as self-assessment or peer-assessment was discussed. Forthcoming research will test and further refine the applied approach of this study to enhance strategic decision-making for sustainability while also considering the role of academia in municipal practices for sustainability.